Correction: Evaluation of copy-number variants as modifiers of breast and ovarian cancer risk for BRCA1 pathogenic variant carriers. (January 2019) - Walker, Logan; Marquart, Louise; Pearson, John; Wiggins, George; O'Mara, Tracy; Parsons, Michael; Barrowdale, Daniel; McGuffog, Lesley; Dennis, Joe; Benitez, Javier; Slavin, Thomas; Radice, Paolo; et al.
This Article was originally published under a CC BY-NC-SA 4.0 license, but has now been made available under a CC BY 4.0 license. The PDF and HTML versions of the Article have been modified accordingly.